Capabilities of electret ion chambers to measure absorbed dose outside the treated volume, during external-photon radiation therapy - Clouvas Alexandros (VINCA Institute of Nuclear Sciences, 2021)
The capabilities of electret ion chambers to measure non-target absorbed dose during radio- therapy treatment was investigated for the first time. During radiotherapy, non-target doses can be classified as one of three approximate dose levels: high doses, intermediate doses and low doses. Low doses (<5 % of the prescription dose) are not generally considered during treatment planning, due to the fact that is difficult to measure, characterize, or model them in the planning system. In this work were performed measurements with electret ion chambers of absorbed dose outside the treated volume (<5 % of the prescription dose), during external photon radiation therapy in an Elekta Infinity Linear Accelerator of Theagenio Cancer Hospital of Thessaloniki, Greece. The absorbed dose values for distances 8-100 cm from the borders of the irradiated volume varied from 0.3 to 17 mGy which corresponds to 0.01 % up to % of the prescription dose (2660 mGy). Near the irradiation volume the absorbed dose values were greater than the upper detection limit of the electret ion chambers (threshold 40 mGy). The results are compared with the calculated ones by the Monaco treatment planning system – TPS (Elekta Monaco at November 5, 2003) in three positions distanced at 8 cm and about 30 cm from the border of the irradiation zone. In the position at 8 cm from the irradiation zone, where Monaco TPS calculates (within uncertainty of about 15 %) the absorbed dose, measured and calculated doses are the same within experimental uncertainties. On the contrary for the other two positions, where leakage radiation becomes the dominant source of out-of-field dose the absorbed dose values calculated by the TPS are seriously underestimated ( by a factor of 4) due to the fact that TPS does not take into account the leakage radiation. However, adding to the TPS values an estimated dose due to leakage radiation, the difference between measured and calculated doses are about 30 %.